Monodisperse Water-Stable Sio2- Coated Fluoride Upconversion Nanoparticles with Tunable Shell Thickness - Tianxing Ji; Xinqiang; Xindong Wang; Qiang Zhou; Guanying Chen (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
Monodisperse water-stable silica functionalization of upconversion nanoparticles are important for their applications in bio-imaging and bio-sensing. Here, we report on the uniform silica coating of NaYF4:Yb,Er,Tm upconversion nanoparticles (UCNPs) with a controlled thickness (3-16 nm) through a modified reverse microemulsion approach. We show that the molar ratio between tetraethylorthosilicate (TEOS) and UCNPs is important to tune the resulting thickness of silica, which can be controlled via simple increase of the concentration of UCNPs while maintaining the TEOS concentration constant. Our results show that those silica-coated upconversion nanoparticles are stable at pH = 7 sodium chloride-free solution, important for their bio-applications.